(untitled) (Nexus International Journal of Science and Education, 2024)
This quantitative non-experimental study employed a descriptive-correlational and predictive approach to investigate the relationship between learning motivation and value expectancy in science, technology, engineering, and mathematics (STEM) among junior high school students. A total of 150 students participated in the survey. The findings revealed that the extent of Junior High School students' learning motivation in terms of self-efficacy, active learning strategies, science learning, performance goal, achievement goal, and learning environment stimulation was extensive descriptive equivalent. Likewise, the extent to which junior high school students value expectations on science, technology, engineering, and mathematics in terms of the perceived value of these fields and expectations for success in science, technology, engineering, and mathematics careers was extensive. A significant relationship between learning motivation and value expectancy in science, technology, engineering, and mathematics among junior high school students. The statistical analysis shows a significant positive relationship between learning motivation and value expectancy in Science, Technology, Engineering, and Mathematics (STEM) among junior high school students in the Davao Oriental division. Active learning strategies and achievement goals are domains of learning motivation that do not significantly influence the value-expectancy of junior high school students' science, technology, engineering, and mathematics.